Discovery of the genus Parawenhoekia Paoli (Acari: Chyzeriidae) in the Western Asian area - Najmeh Kiany; Marjan Seiedy; Masoud Hakimitabar; Martin Husemann (Journal of Insect Biodiversity and Systematics)
We here present the first record of Parawenhoekia aginapaica (Haitlinger, 1999) from Iran, which also represents the first record for the genus of the whole continent (Asia). The specimens were collected in association with an Oedipodinae grasshopper of the genus Aiolopus (Orthoptera: Acrididae). The genus Parawenhoekia Paoli, 1937 has only been known from three Mediterranean countries so far (Italy, Cyprus, and Montenegro) and hence our finding represents a large area extension. This study provides new metric and meristic data and supplements the current knowledge on the species based on new specimens of P. aginapaica collected from Khumeh Zar, Mamasani County, Fars Province, Iran. Photographs of important characteristics are provided. A key to the world species of Parawenhoekia is given.